Urinary Dysfunction in Prostate Cancer A Management Guide - Sandhu, Jaspreet S. (Springer International Publishing : Imprint: Springer, 2016)
This volume provides a comprehensive, state-of-the-art review of this topic.  It reviews natural history, etiology, management, and prevention of urinary dysfunction.  The text covers the multiple new treatments for prostate cancer that have been introduced as well as reviewing the etiology, risk factors, and possible prevention of urinary dysfunction in men with prostate cancer. This textbook  provides a concise yet comprehensive summary of the current status of the field that will help guide patient management and stimulate investigative efforts.  All chapters are written by experts in their fields and include the most up-to-date clinical information       Urinary Dysfunction in Prostate Cancer - A Management Guide will serve as a valuable resource for clinicians, surgeons and researchers with an interest in urinary dysfunction caused by prostate cancer or its treatments.